Photostability of N@C-60 in common solvents - Farrington, B; Hingston, T; Briggs, G; Sambrook, MR; Porfyrakis, K (2011)
Using CW-ESR spectroscopy, the photo induced decomposition of N@C 60 in five solvents under irradiation with 254 nm and 365 nm ultra violet light was measured. The results indicate that the decomposition rate of N@C 60 is highly dependent on the solvent chosen. The finding shows that carbon disulphide and cis/transdecalin are the most suitable solvents for future photoexitation experiments of N@C 60. In addition a comparison between decay rate of N@C 60 in ambient and degassed solvents suggests that decomposition is not principally via an interaction of the 3C 60 excited state and the nitrogen atom. ©The Electrochemical Society.